Former Food and Agro-Industrial By-Products in Dairy Cow Diets: Effects on Milk Quality and Cheese Production - Ludovica Maria Eugenia Mammi; Francesca Ghiaccio; Elisa Benini; Carla Giuditta Vecchiato; Isa Fusaro; Giovanni Buonaiuto; Damiano Cavallini; Alberto Palmonari; Giorgia Canestrari; Riccardo Colleluori; Andrea Formigoni (Animals)
The use of former foodstuff and by-products in cow diets could improve the environmental sustainability of livestock. However, knowledge about the effects of these feeds in ruminant diets on the quality of dairy products is lacking. This study investigated the effects of integrating wheat distillers’ grain with solubles (WDGS) and a former foodstuff product (FFP) into the diet of dairy cows on milk and cheese quality. The environmental impact of the two feeding systems has been evaluated by LCA. A double crossover design was set up with 84 Holstein cows, alternating a control diet and a circular one. In the circular diet, traditional feeds were partially replaced with 4 kg/d WDGS and 3 kg/d FFP. The results showed no effects on dry matter intake and milk yield, while fiber digestibility improved. A reduction in the milk fat content and a modification of the fatty acid profile of milk and cheese were observed. Conversely, cheese yield, composition, and sensory attributes were not affected. The environmental impact of the diet was significantly reduced in terms of land occupation, net fresh water, and global warming potential. These findings suggest that these feeds can be safely included in dairy cow diets. This approach could significantly contribute to reducing greenhouse gas emissions, enhancing the sustainability of the dairy system.